PENINGKATAN KREATIVITAS DAN PRODUKTIVITAS KEGIATAN MEMBATIK DI KELURAHAN TLOGOMAS MALANG - Melany Agustina; Anitarakhmi Handaratri; Kestrilia Rega Prilianti; Sultan Arif Rahmadianto (Universitas Tribhuwana Tunggadewi Malang, 2017)
Batik is one of Indonesian culture heritage that should be preserved.In almost every Indonesia region has batik. Not only batik Jogja or Solo whose name is s become incredibly global, other areas in Indonesia also has batik. Recently, ‘membatik’ community in Kelurahan Tlogomas do not have pattern and a special color which is feature of Malang city .Therefore, activities devotion to community aims to bring training motives and color batik to enrich batik pattern.With community members not more than 10 peoples, this work is hoped can be seeds entrepreneurship that produces advantage. Devotion to community’ team provide socialization, assistance equipment and materials, and created special account to help introduce and markets batik Tlogomas. This activity is also to keep cultural heritage through the improvement of the creativity and productivity membatik activities. Keywords : batik, tlogomas, pattern, color, malang